Anti-obesity and body weight reducing effect of Fortunella japonica peel extract fractions in experimentally obese mice - Lien, Do Ngoc; Quynh, Nguyen Thuy; Quang, Nguyen Hoang; Ngan, Nguyen Thi Thanh (VNU Journal of Science: Natural Sciences and Technology, 2009)
Abstract